PENGARUH LATIHAN PASSING BAWAH BERPASANGAN DAN DRILL INDIVIDU TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI - JAYANTI, KARTIKA DWI (Unnes Journal of Sport Sciences, 2021)
The main problems is often to make mistakes in the underpass technique. The purpose of the study was to find out whether there was an effect of pair bottom passing practice, individual drill and which one had more influence on the volleyball bottom passing ability of the women's volleyball extracurricular participants at SMP Negeri 3 Ungaran. This study uses an experimental method with the form of research design "Pretest-Posttest Group Design". This design is divided into two groups using the formula A-B-B-A. The results of the analysis obtained: 1) t-count = 8.57 > t-table 2.571 (there is an effect of pair-down passing practice), 2) t-count = 4.47 > t-table 2.306 (there is an effect of individual drill exercises), 3.) The pair-down passing exercise is more influential than the individual drill exercise. The conclusions in this study are: 1) Underpassing exercises in pairs with individual drills have a significant effect, 2.) Paired underpassing exercises are more influential in improving the results of female volleyball extracurricular activities at SMP Negeri 3 Ungaran. Suggestions in this study are: the coach of SMP Negeri 3 Ungaran implements paired bottom-passing exercises to improve down-passing abilities.